Laparoscopic Versus Laparotomy Surgical Interventions for Trauma Patients With Single Upper Left Quadrant Penetrating Injuries: Analysis of the American College of Surgeons Trauma Quality Improvement Program Dataset. Issue 9 (September 2022) - Elkbuli, Adel; Newsome, Kevin; Fanfan, Dino; Sutherland, Mason; Bilski, Tracy; Liu, Huazhi; Ang, Darwin
Background: We aim to identify patient cohorts where laparoscopy can be safely utilized with comparable or better outcomes to laparotomy among patients with single penetrating LUQ injuries with a hypothesis that compared to laparotomy, laparoscopy may be associated with equal or improved outcomes of low injury severity patients. Methods: Retrospective review of the ACS-TQP-Participant Use File 2016-2019 dataset. Patients with single LUQ penetrating injuries were included. Primary outcome was risk-adjusted in-hospital mortality. Secondary outcomes included: risk-adjusted complication rates, hospital length-of-stay (H-LOS), and ICU-LOS. Descriptive statistics and multivariable regression with reliability adjustments to account for variations in practice were performed. Results: Of 4149 patients analyzed, 3571 (86.1%) underwent laparotomy, 489 (11.8%) underwent laparoscopy, and 89 (2.1%) underwent laparoscopy-to-laparotomy conversion. Adjusted mortality rates were not significantly different among all study cohorts (P > .05). Compared to laparoscopy, adjusted odds of complications were 4.3-fold higher for all patients who underwent laparotomy and 4-fold higher for laparoscopy-to-laparotomy (LtL) patients (P < .05). Diaphragmatic injuries were associated with significantly increased odds of undergoing LtL, whereas sustaining a colonic injury, gastric injury, hepatic injury, or requiring PRBC transfusions were associated with significantly increased odds of undergoing laparotomy (P < .05). H-LOS (days) was significantly longer for patients who underwent laparotomy compared to laparoscopy (3.9 ± 4.0 vs. 10.8 ± 13.4, P < .0001). Conclusions: Laparoscopy may be considered a viable alternative to laparotomy for hemodynamically stable adult patients with single penetrating LUQ injuries of low injury burden validating our hypothesis. Laparoscopy may be less safe for patients with associated diaphragmatic, colonic, or hepatic injuries.